Perendaman dalam larutan asam askorbat untuk meningkatkan mutu edamame segar (Glycine max L.) - Erwin Nofiyanto; Tri Sono Waluyo; Dewi Larasati (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Edamame is a horticultural crop that is easily damaged. Edamame has limitations because of its characteristic that it easily changes color due to oxidation. Browning can affect the selling price because it reduces its appearance. The study aims to know the influence of gift sour ascorbic in various concentrations on fresh edamame quality (Glycine max (L.) Merrill). Design test study uses design Random complete (RAL). Pattern unidirectional, with one factor that is a difference in concentration sour ascorbic 6 treat and 3 replicates with concentration P1=0 %, P2=1 %, P3=2 %, P4=3 %, P4=4 %, P5=5 % Observed variables _ is shrinking weight, moisture content vitamin c content, texture analyzer TPT, and test organoleptic ( scent, color, texture ). Data obtained analyzed variety and if there is a difference between treatments then tested _ carry on with test Duncan Multiple Range Test (DMRT) at 5 % level. Results study show that treatment takes to effect real ( p0.05) against 9th-day water content and 12th-day TPT%Brix day 9 and day 12, texture analyzer day 9, vitamin C day 9 and 12th day, sensory color day 9 and day 12, sensory aroma day 9 and 12th day and sensory texture day 9 and 12th day However no difference real to shrink weight day 9 and 12th day, difference color day 9 and 12th day and texture analyzer day 12. time edamame storage with addition sour the most optimum ascorbic At test organoleptic treatment P5 (4 %) to most preferred treatment panelists in the parameters of color aroma and texture.